Effective Thermal Property Estimation of Unitary Pebble Beds Based on a CFD-DEM Coupled Method for a Fusion Blanket - 陈磊 陈有华 黄凯 刘松林 (Plasma science & technology, 2015)
Lithium ceramic pebble beds have been considered in the solid blanket design for fusion reactors.To characterize the fusion solid blanket thermal performance,studies of the effective thermal properties,i.e.the effective thermal conductivity and heat transfer coefficient,of the pebble beds are necessary.In this paper,a 3D computational fluid dynamics discrete element method（CFD-DEM） coupled numerical model was proposed to simulate heat transfer and thereby estimate the effective thermal properties.The DEM was applied to produce a geometric topology of a prototypical blanket pebble bed by directly simulating the contact state of each individual particle using basic interaction laws.Based on this geometric topology,a CFD model was built to analyze the temperature distribution and obtain the effective thermal properties.The current numerical model was shown to be in good agreement with the existing experimental data for effective thermal conductivity available in the literature.